MonTerDC: Data Center Thermal Monitoring System - Camillo, Ademir; Pillon, Maurício A.; Miers, Charles C.; Koslovski, Guilherme P. (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2018: Anais do XIX Simpósio em Sistemas Computacionais de Alto Desempenho, 2018)
Information production increment has implied on increasing of the amount and size of Data Centers (DCs) to meet this demand. Creation of small/medium DC has been a common practice adopted by several organizations, as well as large DCs used by public cloud computing providers. Large DC own consolidated monitoring systems, while small and medium DC typlically do not have such systems due to its cost/complexity. We present Monitoramento Termino de Data Centers (MonTerDC), a temperature monitoring solution through sensing which allows to identify thermal zones and its temperatures on standards noncompliance. MonTerDC allows to analyze energy consumption and cooling system together, in order to assist DC administrators on decision making process. Our practical experiments have confirmed the usefulness of MonTerDC while revealing relevant information about thermal behavior in a small DC.